WORK ETHICS IN ISLAMIC PERSPECTIVE - Rokhman, Wahibur (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2011)
The collapse of large corporations such as Enron, Arthur Anderson, WorldCom, Global Crossing for mega scandal makes the work ethic got a very big concern in the business world. This shows that as good and professional as any management company is not otherwise based on the good work ethic there will be manipulations that result in bankruptcy. The concept of work ethic was first developed by Max Weber in a book entitled The Protestant Ethic and the Spirit of Capitalism, associating the success of the capitalist system with Protestant teachings. Furthermore, Weber also argues that the Muslim community can not progress in the economic field due to various reasons such as Sufism, the attitude of fatalism and outokratik the Islamic kingdoms. The concept of Islamic work ethics is a form of response from experts Muslim experts in the field of human resources and organizational theory on the criticism Weber. Various studies conducted Aslam (2000; 2001) in Turkey, Ali (1996) in the US shows that there is a significant influence of Islamic work ethics on work productivity in Muslim society.